The role of consumer satisfaction on the culinary business prospects of potato donuts - Samari Samari; Dodi Kusuma Hadi Soejoko; Sigit Ratnanto; Hery Purnomo; Cindya Alam Prameswari Putri (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to identify the direct effects of taste, product quality perception, and product attributes on purchasing decisions and consumer satisfaction, as well as the indirect effects of these factors on consumer satisfaction through purchasing decisions. The urgency of research that businesspeople know the power of these variables in terms of decisions and customer satisfaction, so that they can develop strategies to survive in this business. Using quantitative methodology, with a sample of 50 respondents, the sampling strategy uses the non-probability sampling method. Multiple linear regression analysis and the Sobel test are the data analysis techniques used. Research findings state that perceptions of product quality and product attributes do not significantly influence purchasing decisions, and these purchasing decisions cannot mediate to consumer satisfaction of potato donuts.